A value-added view of intellectual capital and financial performance in knowledge management: a case of Chinese insurance companies - Ren, Chunya; Ting, Irene Wei Kiong; Kweh, Qian Long (Inderscience Enterprises Ltd., 2021)
Intellectual capital (IC) has a strong linkage to knowledge management thus influencing financial performance. Using resource-based view theory, this paper aims to explore the relationships between intellectual capital and financial performance based on the data of 220 Chinese insurance companies listed in China Insurance Yearbook, from 2008 to 2017. Our study is robust for using Value-Added Intellectual Coefficient (VAICTM) and ratios as the proxies of IC, as well as return on assets and return on equities as the proxies of financial performance. Panel data regression and ordinary least squares are applied to analyse the data. Apart from the popular direct effect, we also find significant positive (negative) effects of increasing (decreasing) IC on increasing (decreasing) financial performance. However, we find no dynamic relationship between IC and financial performance. This paper provides scholars and practitioners with new perspectives on IC learning and management.